Transformations of popular terms and meanings in sports-specific contexts: opinion poll - Berdysheva, N. Y.; Murtazina, G. Kh.; Boykova, N. G.; Karazhaeva, M. B.; Golokova, M. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze meanings of the term `sports aggression` in the sporting young people`s communities.